1992
DOI: 10.1126/science.1570514
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Tyrosine Phosphorylation in the Cytopathic Effect of Human Immunodeficiency Virus-1

Abstract: Protein tyrosine phosphorylation is a common mechanism of signaling in pathways that regulate T cell receptor-mediated cell activation, cell proliferation, and the cell cycle. Because human immunodeficiency virus (HIV) is though to affect normal cell signaling, tyrosine phosphorylation may be associated with HIV cytopathicity. In both HIV-infected cells and transfected cells that stably express HIV envelope glycoproteins undergoing HIVgp41-induced cell fusion, a 30-kilodalton protein was phosphorylated on tyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…This could allow the phosphorylation process to start at the proper time. For example, it has been shown that the interaction between gp120 and CD4 is able to activate cellular kinases implicated in signal transduction (55)(56)(57)(58)(59). One of these kinases could be the stimulus useful to trigger the phosphorylation of CAp24 and thus the disassembly of viral core.…”
Section: Discussionmentioning
confidence: 99%
“…This could allow the phosphorylation process to start at the proper time. For example, it has been shown that the interaction between gp120 and CD4 is able to activate cellular kinases implicated in signal transduction (55)(56)(57)(58)(59). One of these kinases could be the stimulus useful to trigger the phosphorylation of CAp24 and thus the disassembly of viral core.…”
Section: Discussionmentioning
confidence: 99%
“…Our data, obtained in a normal Thl clone, are clearly in agreement with these last results. Although further work is needed to identify the specific PTKs involved in gpl20-apoptosis, the possibility of using PTK inhibitors for AIDS therapy is attractive, since they could reduce CD4+ cell apoptosis as well as interfere with virus replication [34] and its cytopathic effect [35].…”
Section: Time (H)mentioning
confidence: 99%
“…Experimental observations in vitro describe several phenomena that might independently contribute to the cell death in vivo. Cytopathicity can be a direct consequence of viral replication inside infected lymphocytes (2)(3)(4)(5). Induction of apoptosis by HIV-1 has been suggested as a cause of the depletion of infected CD4+ cells (6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%